Trauma and the default mode network: review and exploratory study - Chan, Aldrich; Harvey, Philip; Hernandez-Cardenache, Rene; Alperin, Noam; Lee, Sang; Hunt, Christopher; Petersen, Nick; Northoff, Georg; Robertson, Nadine; Ouyang, Jason; Karasik, Ryan; Williams, Kate (Frontiers in Behavioral Neuroscience, 2024)
While PTSD continues to be researched in great depth, less attention has been given to the continuum of traumatic responses that resides outside this diagnosis. This investigation begins with a literature review examining the spectrum of responses through the lens of the default mode network (DMN). To build upon this literature, a systematic exploratory study was incorporated, examining DMN-related neuropsychological functioning of 27 participants (16 trauma-exposed, and 11 non-trauma-exposed), with a subset (15 participants) completing neuroimaging. This study revealed that in comparison to the control group, the trauma-exposed group had reductions in their capacity for self-referential processing, social cognition, autobiographical recall, prospection, and increased mind-wandering. While correlations were encountered between cognitive findings and brain volume, comparative volumetric findings between trauma-exposed and non-t rauma exposed were insignificant. This suggests that the conservation of DMN structural integrity may play a role in resilience, supporting the existing theory that reduced hippocampal volume may be a pre-existing vulnerability to PTSD rather than a consequence and that reductions in DMN related cognition are functionally mediated.